3D finite elements to model electromechanical coupled solids at failure. Issue 1 (December 2013) - Linder, Christian
Abstract This work presents an extension of newly developed 3D finite elements to model failure in purely mechanical based materials [1, 2] to electromechanical coupled materials. Following the approach suggested in [6] for the plane setting, new finite elements are developed, which in addition to resolving strong discontinuities in the mechanical displacement field are capable of modeling strong discontinuities in 3D also in the electric potential. An application to a 3D off‐centered three point bending test under combined mechanical and electrical loading outlines the performance of the newly developed finite elements. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)